"Personal @ business" businesses'/companies' assets as matrimonial property; the legal policy - Abd Ghadas, Zuhairah Ariff; Ibrahim, Norliah (2010)
Matrimonial disputes are one area of law, which is highly litigated before the registrars and judges. Under the Malaysian law, the court shall have power to order the division of any assets acquired by the divorced parties during the marriage including those attained by the sole efforts of one part to the marriage. Reference to personal property normally did not raise contentious issue as the court would apply the general rule / method in dividing or concluding the matrimonial property